A pragmatic, single-arm clinical trial of a dose modification algorithm for preventing cytopenia-related delays during FOLFOX chemotherapy - Wright, Heather N.; Tosteson, Tor D.; Hourdequin, Kathryn C.; Ripple, Gregory H.; Fuld, Alexander D.; Dragnev, Konstantin H.; Amin, Manik; Muralikrishnan, Sivraj; McGrath, Elizabeth B.; Stannard, Maureen G.; Schofield, Lora L.; Lord-Halvorson, Sierra; et al. (Supportive care in cancer, 2025)
Purpose Unplanned delays are common during FOLFOX chemotherapy. We evaluated a novel FOLFOX dose modification algorithm designed to reduce unplanned delays while maintaining dose intensity. Methods We conducted a pragmatic, single-arm clinical trial to evaluate PAGODA, a proactive graduated dose modification algorithm for FOLFOX chemotherapy (NCT04526886). The algorithm prescribes chemotherapy dose reductions and delays based on absolute neutrophil count (ANC) and platelet count. Patients receiving FOLFOX-based chemotherapy were eligible. Participants received standard chemotherapy doses in cycle 1 (bolus 5-FU 400 mg/m 2 , oxaliplatin 85 mg/m 2 , and infusional 5-FU 2400 mg/m 2 /46 h). The primary outcome was unplanned delay prior to cycle 6 (> 18 days between cycles). We compared the incidence of unplanned delay against the historical proportion of 43%. Relative dose intensity (RDI) was a key secondary outcome. Results There were 48 evaluable participants. The median age was 66, and 50% were female. The most common primary cancer sites were colorectal ( n = 31) and gastroesophageal ( n = 12). Sixteen of 48 subjects had any unplanned delay before completing cycle 6 (33%, 95% CI 0.22–0.47, p = 0.18 for comparison with the historical proportion) and seven subjects had any cytopenia-related delay (15%, CI 0.07–0.27). Seven cycles were delivered without delay with an ANC of 750–999/µl. The mean chemotherapy RDIs were: oxaliplatin, 86%; infusional 5-FU, 92%; and bolus 5-FU, 65%. Conclusions The PAGODA dose modification algorithm was safe and was associated with a low rate of cytopenia-related delays. Further intervention refinement and testing may help to reduce unplanned delays and attendant time toxicity. Trial registration Registered at ClinicalTrials.gov on August 21, 2020. ClinicalTrials.gov ID: NCT04526886.